PENGARUH LINGKUNGAN KERJA SOSIAL DAN PELATIHAN TERHADAP KINERJA PEGAWAI LAPANGAN PT. ADHI KARYA AREA JAKARTA SELATAN - Davied Andri Shandy, - (2022)
Companies are required to always maintain employees to show good performance and maintain employees in order to dedicate themselves to the organization. Companies in various industries in many countries still face employee performance problems, be it manufacturing or service industries, the results show that the industry has low performance. One of the companies that experienced a decline in performance was PT. Adhi Karya Jakarta. There are several strategies to improve employee performance by improving the Social Work Environment and Job Training. This research aims to find out 1) social work environment conditions 2) the effectiveness of job training 3) employee performance levels 4) Knowing the influence of the social work environment on the performance of employees 5) Knowing the effect of job training on employee performance. This research uses quantitative methods. The sample technique used is a saturated sample of 123 employees. The data analysis technique used is Multiple Linear Regression. The results of the study can be known that 1) The social work environment is at a strong level 2) Training is at a strong level 3) Employee Performance is strongly stigmatized 4) Social Work Environment has an influence of 35.7% on performance 5) Training has an influence of 49.5% on performance. The Company continues to improve the relationship and development of employee capabilities by hosting gathering activities, social events, seminars or sharing with other branch offices. It is expected to make practical contributions through input or advice in the business field regarding social work environment, training, and employee performance.